2020
DOI: 10.1039/d0cs00021c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of block copolymers towards mesoporous materials for energy storage and conversion systems

Abstract: This paper reviews the progress in the field of block copolymer-templated mesoporous materials, including synthetic methods, morphological and pore size control and their potential applications in energy storage and conversion devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
298
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(301 citation statements)
references
References 431 publications
2
298
0
1
Order By: Relevance
“…Nevertheless, in this case, the drawbacks are that there is no ordering of the nanopores or control over their actual position, and also that an ion accelerator is needed to produce the tracks 72 . Other kinds of widely used nanoporous structures in current research, apart from AAOs, are porous polymers, such as block copolymers 73 or metal-organic frameworks (MOFs) 74 , which provide a high surface to volume ratio, but they also have limited thermal stability, with none of them able to work over 600º C 75 , and limited thickness of the achieved nanostructures. Also, the research on mesoporous silica 76 is quite relevant, but in this case, mostly silica nanoparticles (100 to 500 nm in diameter) with a porous surface (ranging from 2 to 50 nm in diameter) are employed, which gives rise to different architectures than those obtained with AAOs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in this case, the drawbacks are that there is no ordering of the nanopores or control over their actual position, and also that an ion accelerator is needed to produce the tracks 72 . Other kinds of widely used nanoporous structures in current research, apart from AAOs, are porous polymers, such as block copolymers 73 or metal-organic frameworks (MOFs) 74 , which provide a high surface to volume ratio, but they also have limited thermal stability, with none of them able to work over 600º C 75 , and limited thickness of the achieved nanostructures. Also, the research on mesoporous silica 76 is quite relevant, but in this case, mostly silica nanoparticles (100 to 500 nm in diameter) with a porous surface (ranging from 2 to 50 nm in diameter) are employed, which gives rise to different architectures than those obtained with AAOs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low reserve, high cost, and poor stability of precious metals catalysts limit their commercial applications. Therefore, the investigation of high efficiency, low cost and stable noble metal‐free electrocatalysts is imperatively meaningful and transition metal‐based catalysts emerged owing to their moderate catalytic activity and tunable electronic structures to optimize the adsorption of intermediates during the reaction process [22–26] …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the investigation of high efficiency, low cost and stable noble metal-free electrocatalysts is imperatively meaningful and transition metal-based catalysts emerged owing to their moderate catalytic activity and tunable electronic structures to optimize the adsorption of intermediates during the reaction process. [22][23][24][25][26] Reducing the content of metals is a valid method to reduce the cost of transition metal-based electrocatalysts. In order to maintain the high activity of catalysts when the loading of metal is decreased, it is necessary to improve the utilization rate of metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Electric double layer capacitors (EDLCs), a typical type of supercapacitors, are appealing power sources for consumer electronics and uninterruptible power supplies owing to their high power density, rapid charge/discharge, environmental friendliness, and long cycling life (Simon and Gogotsi, 2008 , 2020 ; Choi et al, 2012 ; Wang et al, 2012 ; Liu et al, 2019 , 2020 ; Noori et al, 2019 ; Li et al, 2020 ). Porous carbon materials have attracted tremendous attention as electrode materials for supercapacitors because of their high specific surface area, high conductivity, high chemical stability and tunable porous structures (Zhai et al, 2011 ; Tian et al, 2016 , 2018 ; Hou et al, 2018 ; Wang et al, 2018 ; Liu et al, 2019 ; Shao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The partially inaccessible small micropores also decreased the rate performance of microporous carbon (Zhang and Zhao, 2009 ). In the past decades, mesoporous carbon materials with pore sizes of 2–50 nm have become promising candidates for EDLC applications (Simon and Gogotsi, 2008 , 2020 ; Zhai et al, 2011 ; Choi et al, 2012 ; Wang et al, 2012 , 2018 ; Tian et al, 2016 , 2018 ; Hou et al, 2018 ; Liu et al, 2019 , 2020 ; Noori et al, 2019 ; Li et al, 2020 ; Shao et al, 2020 ). Huang et al ( 2008 ) demonstrated that the capacitance normalized by surface area was higher in mesoporous carbon compared to microporous carbon in aqueous solutions, suggesting a high capacitance can be achieved in carbon materials with high mesoporous surface area.…”
Section: Introductionmentioning
confidence: 99%